2013
DOI: 10.5455/2319-2003.ijbcp20131010
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of dexmedetomidine vs midazolam for sedation and hemodynamic changes during tympanoplasty and modified radical mastoidectomy

Abstract: Background: The benzodiazepine, Midazolam, has been used medication given for sedation in tympanoplasty and mastoidectomy because of a number of beneficial effects. However, Dexmedetomidine is a highly selective α2-adrenoceptor agonist is emerging as preferred choice now a day. The aim of the study is to compare hemodynamic stability and sedation under Dexmedetomidine vs Midazolam during tympanoplasty and modified radical mastoidectomy done under local anaesthesia. Methods: After obtaining ethics clearanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…Fentanyl IV intraoperatively and Inj. Diclofenac IV postoperatively) which is concordance with previous studies [12,[16][17][18] suggesting analgesic effect of dexmedetomidine was better than midazolam in perioperative period in patients undergoing surgery with LA and MAC. When compared with midazolam, dexmedetomidineinduced bradycardia was not statistically significant and was not found to be clinically challenging.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Fentanyl IV intraoperatively and Inj. Diclofenac IV postoperatively) which is concordance with previous studies [12,[16][17][18] suggesting analgesic effect of dexmedetomidine was better than midazolam in perioperative period in patients undergoing surgery with LA and MAC. When compared with midazolam, dexmedetomidineinduced bradycardia was not statistically significant and was not found to be clinically challenging.…”
Section: Discussionsupporting
confidence: 91%
“…These results are correlated well with the earlier studies [22,23] . Parikh et al [4] and Vyas [5] and demonstrated significant higher surgeon's satisfaction score in group D than in group M in their studies. But in present study, the surgeon satisfaction score of 4-5 was achieved among 80.0% of surgeons in both the groups.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Sedation and analgesia here are achieved with either midazolam or dexmedetomidine in modern day-care surgeries. Dexmedetomidine is a new drug which acts on α2-adrenergic receptors in the dorsal horn of the spinal cord to produce adequate analgesia and It has been reported to significantly reduce the opioid requirements both during and after surgery, according to Verma et al 12 Compared with midazolam, it gives better haemodynamic stability and patient satisfaction according to a study by Vyas et al 13 Various published studies suggest that dexmedetomidine provides adequate sedation with analgesia and good surgical and patient comfort without any adverse effects for patients undergoing tympanoplasty under local anaesthesia. The amount of blood loss during surgery, which also amounts to a better oligaemic field, especially in middle ear surgery was also significantly lesser with this drug in a study by Gupta et al 14 Propofol usually used in the induction of GA is associated with the increased requirement of post-operative rescue analgesic and increased intraoperative hemodynamic instability (hypotension).…”
Section: Discussionmentioning
confidence: 99%